Association Between Vitamin D and Novel SARS-CoV-2 Respiratory Dysfunction – A Scoping Review of Current Evidence and Its Implication for COVID-19 Pandemic - Santaolalla, Aida; Beckmann, Kerri; Kibaru, Joyce; Josephs, Debra; Van Hemelrijck, Mieke; Irshad, Sheeba (Frontiers in Physiology, 2020)
Objectives: To assess the association between vitamin D deficiency and increased morbidity/mortality with COVID-19 respiratory dysfunction. Design: Scoping review Data Sources: Ovid MEDLINE (1946 to 24 of April 2020) and PubMed (2020 to 17 of September 2020) Eligibility criteria for selecting studies: A search using the search terms: ((cholecalciferol or ergocalciferol or vitamin D2 or vitamin D3 or vitamin D or 25OHD) and (SARS-CoV-2 or coronavirus or COVID or betacoronavirus or MERS-CoV or SARS-CoV or respiratory infection or acute respiratory distress syndrome or ARDS))m.p. was conducted on the 24/04/2020 (Search A) and 17/09/2020 (Search B). Results: 91 studies were identified as being concerned with Acute Respiratory Infection (ARI)/Acute Respiratory Distress Syndrome (ARDS) and vitamin D, and 25 publications specifically explored the role of vitamin D deficiency in the development and progression of SARS-CoV-2/COVID-19 related ARDS. Search “A” identified three main themes of indirect evidence supporting such an association. Consistent epidemiological evidence exists linking low vitamin D levels to increased risk and severity of respiratory tract infections. We also report on plausible biological processes supporting such an association; and present weaker evidence supporting the benefit of vitamin D supplementation in reducing the risk and severity of ARIs. Uncertainty remains about what constitutes an appropriate dosing regimen in relation to reducing risk/severity of ARI/ARDS. More recent evidence (Search B) provided new insights into some direct links between vitamin D and COVID-19; with a number of cohort and ecological studies supporting an association with PCR-positivity for SARS-CoV-2 and vitamin D deficiency. The exact efficacy of the vitamin D supplementation for prevention of, or as an adjunct treatment for COVID-19 remains to be determined; but a number of randomised control trials (RCTs) currently underway are actively investigating these potential benefits. Conclusions: Our rapid review of literature supports the need for observational studies with COVID-19 infected populations to measure and assess vitamin D levels in relation to risk/severity and outcomes; alongside RCTs designed to evaluate the efficacy of supplementation both in preventive and therapeutic contexts. The overlap in the vitamin D associated biological pathways with the dysregulation reported to drive COVID-19 outcomes warrants further investigation.